1984
DOI: 10.1002/jca.2920020205
|View full text |Cite
|
Sign up to set email alerts
|

Use of erythrocytapheresis in the treatment of patients with sickle cell anemia

Abstract: We performed exchange transfusions, utilizing the technique of automated erythrocytapheresis, for the treatment of patients with sickle cell anemia. In an attempt to determine guidelines for the use of erythrocytapheresis, we studied the use of this procedure in three distinct clinical situations in nine patients with sickle cell disease. Patients with dangerous complications of sickle cell disease such as acute respiratory distress and priapism responded well to erythrocytapheresis, showing marked improvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…In our view, the underlying biological effects of both procedures have not been fully explored and the clinical benefits have not been compared [40][41][42][43]. We used this window of opportunity to examine other possible therapeutic benefits of a manual exchange transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…In our view, the underlying biological effects of both procedures have not been fully explored and the clinical benefits have not been compared [40][41][42][43]. We used this window of opportunity to examine other possible therapeutic benefits of a manual exchange transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Significant respiratory distress or clinical decompensation, hemoglobin !2 g/dL below baseline, and oxygen saturation .5% below baseline are all indications for packed red blood cell (PRBC) transfusion (Miller 2011). Automated erythrocytapheresis should be used for severe ACS associated with significant respiratory distress or hypoxia (Kleinman et al 1984;Velasquez et al 2009). There is no current evidence that inhaled nitric oxide (NO) has a beneficial role in the current management of ACS (Gladwin et al 1999;Al Hajeri et al 2008), but several clinical trials are ongoing.…”
Section: Acute Chest Syndromementioning
confidence: 99%
“…Although less desirable than hydroxyurea treatment, transfusion or exchange transfusion programmes are sometimes used to control the frequency of vaso‐occlusive events ( Leitman et al , 1991 ; Wayne et al , 1993 ; Davies & Olatunji, 1995). The rationale for the transfusion approach is based on the following laboratory and clinical observations: (a) adding even small quantities of Hb AA red cells to Hb SS red cells in vitro improves the rheologic characteristics of the mixture ( Lessin et al , 1978 ); (b) in SS children with hyposthenuria or functional asplenia transfusions can temporarily reverse these abnormalities ( Statius van Eps et al , 1970 ; Pearson et al , 1970 ; Wethers & Grover, 1987); (c) exchange transfusions improve exercise capacity in SS patients without substantially raising their haematocrit ( Miller et al , 1980 ), suggesting that addition of non‐sickling RBCs improves blood rheology and hence tissue perfusion; (d) vaso‐occlusive complications such as pain crises, chest syndrome and priapism are considered rare in children with sickle cell anaemia who are on transfusion programmes for stroke; (e) a prospective randomized trial showed that prophylactic transfusions reduced the incidence of vaso‐occlusive events in pregnant sickle cell patients ( Koshy et al , 1988 ).…”
Section: Decreasing the Frequency Of Vaso‐occlusive Events: Transfusimentioning
confidence: 99%